The Paradox of Victims’ Perceptions and Knowledge against Flood Causes - Samsurijan, Mohamad Shaharudin; Iskandar, Eddy; Jamir Singh, Paramjit Singh; Abdul Latiff, Abdul Rais; Ali Yasah, Muhammad Fikri (Asian Social Work Journal, 2024)
This study aims to unravel the paradox of perceptions and knowledge of the flood victims towards the causes of the disaster in the context of internal and external. Internal context comprises of a comparison of perceptions and knowledge based on individual characteristics (age, gender, education and income). Whereas, the external context includes the factors of the awareness of the victims towards the amount of rainfall, the impact of land use changes as well as the negligence of the responsible parties. The main objective of this study is to determine the differences of perception and knowledge of December 2014 flood victims in Kelantan towards the factors that lead to the flood. This disaster had resulted in huge amount of money lost as well as traumatize the victims in which can be felt to this day. Since that incident, there were various points of view and different perceptions in finding the cause of the disaster occurred. Besides that, the study found that the level of perception and knowledge as to the cause of the disaster is different in the context of the internal (individual characteristics). This difference has a significant influence on the awareness of the causes of the floods that occurred in the external context. Significant relationships at the level of p<0.05 has existed between perception and knowledge of the causes of the disaster victims affected by environmental changes in the last 10 years. This indicates that although the victim is aware of the physical environment changes happening around them, but all that is seen is not a major contributing factor to the cause of the floods in Kelantan in 2014.